Productivity Promises, Precarious Realities: Ethnographic Study of Harm Reduction Implementation in Indonesia - Sari Damar Ratri (Antropologi Indonesia, 2015)
AbstractThis monograph examines the implementation of harm reduction programs in Indonesia that failed to improve the quality of drug users’ lives. The failure is the result of programs that merely provide drug users with instrumental strategy to deal with addiction through substitution therapy. The designation of legal substances such as methadone and subuxone is only to replace illegal drug addiction. In the end, the program fails to provide drug users with sufficient information to manage their dependence and even leads them to uncontrolled poly-substance use. This three months of ethnographic fieldwork focuses on examining Harm Reduction (HR) experiences in both methadone and subuxone users. The users are still stigmatized, although they are no longer illegal drug users. It is caused by the fact that HR only promotes rationalism and pragmatism in the contemporary drug treatment. This stigma results in socioeconomic exclusion which limits the access to lead livable lives for users. It became apparent that instead of improving users’ life quality, HR programs continuously reproduce the precariousness of drug users’ lives.Keywords: harm reduction, drug users, interventions, precarious, productivity, Indonesia